Dynamic optimization of a composite material robot arm using a flexible link and joint model - Marwah Ghazi Kareem; M. Abdularazza; Kawther K. Younus; Husam Jawad Abdulsamad; Luay S. Al-Ansari (Results in Engineering, 2025)
The study aims to optimize the design of a six-degree-of-freedom robotic arm using advanced composite materials specifically carbon/polyester fiber-reinforced composites to achieve a lightweight yet stiff structure with superior dynamic performance. The main contribution of this article is the development of a dynamic optimization framework that integrates a gradient-based optimization technique with the finite element method (FEM) to model and analyze the flexible robotic arm incorporating flexible joints. This approach carefully derives the equations of motion to fully capture all dynamic coupling effects within the system including the influence of joint torsional stiffness on both flexible links and joints. The optimization process focuses on minimizing the overall displacement while reducing the robot arm’s mass, inertia and enhancing its dynamic capabilities. Using the block Lanczos method implemented in MATLAB R2021a to calculate the natural frequencies and compares the original aluminum design with the optimized composite arm. The results demonstrate a significant improvement in stiffness along with a notable reduction in mass and inertia. Consequently, the optimized robot arm achieves exceptional specific stiffness, strength and enabling an increase in the load capacity at the end effector by up to 30 %.